Clear evidence for element partitioning effects in a Ti–6Al–4V alloy by the first-principles phase field method. (31st March 2020) - Pham, T N; Ohno, K; Sahara, R; Kuwahara, R; Bhattacharyya, S
Abstract: Ti–6 wt% Al–4 wt% V (Ti64) is an α + β titanium alloy, in which the alloying components strongly affect the mechanical properties. In this report, element partitioning effects in Ti64 are investigated by using the first-principles phase field (FPPF) method, which has recently been proposed by our group. In the FPPF method, the local free energy is calculated using a cluster expansion method in combination with density functional theory and the temperature effect is incorporated using potential renormalization theory. We have succeeded in identifying enrichment of Al (V) in the α ( β ) phase, i.e., the clear evidence for the element partitioning effects of Al and V, without using any thermodynamical parameter. The transformation of the β phase and the α phase in microstructure is investigated by varying the V and Al concentrations by a small amount. Our results are in excellent agreement with the recent experimental results, showing the validity of the FPPF method for ternary alloys.